Community Implementation of Early Behavioral Intervention: Higher Intensity Gives Better Outcome. Issue 1 (2nd January 2020) - Eldevik, Sigmund; Titlestad, Kristine Berg; Aarlie, Hege; Tønnesen, Roy
ABSTRACT: We evaluated the outcome of early behavioral intervention for children with Autism Spectrum Disorders (ASD) as it was provided through public service providers in Norway. A group of 21 children received low-intensity intervention (11.1 weekly hours), a second group of 36 children higher intensity intervention (18.1 weekly hours), and a third group of 17 children received eclectic special education. Group assignment was based on independent referrals. We compared outccromes on adaptive behavior, ASD severity, and intellectual functioning after one year. The lower and higher intensity behavioral intervention groups received fewer hours than what is recommendedbut did significantly better than the eclectic group. Moreover, the higher intensity behavioral group did better than the lower intensity behavioral group. Nevertheless, gains in both groups were more modest than what is reported for intervention that is more intensive. W 3e describe the model of service delivery, discuss challenges with it, and propose improvements.